Predictors of change in carotid atherosclerotic plaque inflammation and burden as measured by 18-FDG-PET and MRI, respectively, in the dal-PLAQUE study - Mani, Venkatesh (2014)
Baseline predictors of response to treatment of patients with coronary heart disease (CHD) with respect to vascular inflammation and atherosclerotic plaque burden are poorly understood. From post hoc analysis of the dal-PLAQUE study (NCT00655473), 18F–fluorodeoxyglucose-positron emission tomography (18-FDG-PET) imaging and carotid black blood magnetic resonance imaging (MRI) were used to track changes in these vascular parameters. Baseline demographics, imaging, and biomarkers were collected/measured in 130 patients with CHD or CHD risk-equivalents, and imaging follow-up at 6 months (PET) and 24 months (MRI) was performed. Using stepwise linear regression, predictors of change in carotid plaque inflammation by PET [target-to-background ratio (TBR), n = 92] and plaque burden by MRI [wall area (WA) and total vessel area (TVA), n = 89] were determined. Variables with p < 0.05 in multivariable models were considered independently significant. Interleukin-6, systolic blood pressure and standard deviation of wall thickness (WT) at baseline were independently positively associated with 18-FDG uptake (mean of maximum [MeanMax] TBR change over 6 months). Mean of mean TBR, phospholipase A(2), apolipoprotein A-I, and high-sensitivity C-reactive protein at baseline were independently negatively associated with MeanMax TBR change over 6 months. Mean WT and plasminogen activator inhibitor-1 (PAI-1) activity at baseline, and age, were independently associated with change in WA over 24 months. For TVA changes; mean WA and PAI-1 activity at baseline, age, and female gender were independent predictors. These findings may help determine patients most suitable for clinical trials employing plaque inflammation or burden changes as endpoints.